Tissue-Adhesive and Biocompatible Zein-Polyaniline-Based Hydrogels for Mechanoresponsive Energy-Harvesting Applications - Maduru Suneetha; Seainn Bang; Sarah A. Alshehri; Sung Soo Han (Gels)
Flexible, biocompatible, and adhesive materials are vital for wearable strain sensors in bioelectronics. This study presents zein-polyaniline (ZPANI) hydrogels with mechanoresponsive energy-harvesting properties. SEM revealed a sheet-like fibrous morphology, enhancing adhesion. Incorporating 0.5 wt% polyaniline (PANI) introduced nanostructured aggregates, while higher PANI concentrations (3–5 wt%) formed intertwined fibrous networks, improving the mechanical integrity, surface area, and conductivity. PANI enhanced electrical conductivity, and the hydrogels displayed excellent swelling behavior, ensuring flexibility and strong tissue adhesion. Biocompatibility was validated through fibroblast cell culture assays, and the adhesive properties were tested on substrates, such as porcine skin, steel, and aluminum, demonstrating versatile adhesion. The adhesion strength of hydrogels to porcine skin was greatly enhanced with an increasing amount of PANI. The maximum adhesion strength was found to be 30.1 ± 2.1 kPa for ZPANI-5.0. Mechanical testing showed a trade-off between strength and conductivity. The tensile strength decreased from 13.4 kPa (ZPANI-0) to 7.1 kPa (ZPANI-5.0), and the compressive strength declined from 18.5 kPa to 1.6 kPa, indicating increased brittleness. A rheological analysis revealed enhanced strain tolerance (>500% strain) with an increasing PANI content. The storage modulus (G′) remained stable up to 100% strain in PANI-free hydrogels but collapsed beyond 450% strain, while PANI-containing hydrogels exhibited improved viscoelasticity. Mechanical testing showed robust voltage output signals under compression within a 20 s response time. Despite the reduced mechanical strength, energy-harvesting tests showed a surface power density of 0.12 nW cm−2, charge storage of 0.71 nJ, and a surface energy density of 1.4 pWh cm−2. The synergy of the piezoelectric response, bioadhesion, and tunable viscoelasticity establishes ZPANI hydrogels as promising candidates for wearable sensors and energy-harvesting applications. Optimizing the PANI content is crucial for balancing mechanical stability, adhesion, and electrical performance, ensuring long-term bioelectronic functionality.